Soil Liquefaction in Padang due to Padang Earthquake 30September 2009 - Hakam, A. (Institute of Research and Community Outreach - Petra Christian University, 2012)
The Padang earthquake of M7.6 on 30 September 2009 (30S’09) caused damage to buildings, houses, public water facilities, and road ways. Several buildings were damaged due to liquefaction. This paper describes the liquefaction potential in Padang based on the site observation and analytical examination. The liquefaction was observed at a number of sites including roadway, river bank and play ground. The samples of sand boils were sent to the laboratory to determine the soil grain size distributions. It is found that the fine-sand (diameter less than 0.4 mm) content of the liquefied soil samples is more than 65%. This type of soils satisfies the criteria of liquefaction susceptibility. Based on the field soil test data, the liquefaction potential of sites is also examined. The results show that the observed locations have liquefaction potential.